The Effectiveness of Animation Video in Teaching Vocabulary towards Mastery at the 2ND Grade of SMPN 16 MATARAM - Sari, Wisha Aulia; Farmasari, Santi; Putera, Lalu Jaswadi (Jurnal Ilmiah Profesi Pendidikan, 2026)
This study aimed to determine the effectiveness of using animation videos as a teaching medium to improve students’ vocabulary mastery at SMPN 16 Mataram. The study addressed the problem of low vocabulary achievement caused by conventional and less engaging teaching methods in English classrooms. A quantitative approach was employed using a pre-experimental one-group pre-test and post-test design. The sample consisted of 32 eighth-grade students of class VIII C in the academic year 2024/2025. The instrument used was a validated vocabulary test comprising 20 items in the form of multiple-choice and matching questions. The data were analyzed using a paired sample t-test with the assistance of SPSS 25. The results showed a significant improvement in students’ vocabulary scores, with the mean score increasing from 58.91 in the pre-test to 85.63 in the post-test. The significance value (Sig. 2-tailed) was 0.000, which was lower than 0.05. These findings indicate that animation videos provide an engaging learning experience and effectively enhance students’ vocabulary mastery at the junior high school level.